The effects of the timing and method of logging on forest structure in Peninsular Malaysia - Ho Wei, Seng; Wickneswari, Ratnam; Shukor, Mohamad Noor; Mahani, Mansor Clyde (Elsevier, 2004)
We investigated the effects of immediate, short-term (2.5 years after logging) and long-term (about 50 years after logging) logging on tree species from different diameter size classes in three forest reserves in Peninsular Malaysia. Demographic data on number of trees, species and diameter of all trees above 1 cm diameter at breast height (dbh) were measured from three ecological plots (20 m × 50 m) established at different elevations in each study site. The total reduction in mean basal area for trees ≥1 cm dbh for both logged stands was significantly different (P < 0.05), i.e. 50.9% in Compartment 118 and 51.8% in Compartment 48. All trees more than 60 cm dbh in Compartment 118 and 75 cm dbh in Compartment 48 were felled in a single selective cutting under selective management system (SMS). The removal of these genetically superior adult trees will affect the genetic quality of the remaining and subsequent regenerating gene pools. The mean basal area and tree density for seedling and sapling class (<5 cm dbh) were reduced to one-half of the original stand in Compartment 118 after logging, meanwhile an increment of 24.3% was observed in Compartment 48, 2.5 years after logging. This implies that the logging operation favoured the growth of seedlings and saplings. The net loss in trees was offset by incremental growth in surviving trees. Good regeneration was observed in the regenerated stand of Compartment 69 (RS-C69) with 28.5% and 20.5% more, respectively, in basal area and tree density for seedling and sapling class compared to Compartment 118 before logging. There were no distinct changes in species composition before and after logging in this study. The high negative correlation of basal area with relative disturbance index was observed in Compartments 118 and 48 based on botanical name or native name, indicating that the degree of disturbance was affected by the type and magnitude of disturbances in each of the localities in the compartment. This further implies that a logging operation in the compartment is not a homogeneous activity. The current harvesting system (i.e. SMS) in Peninsular Malaysia should consider the abundance of young regenerants and the genetic quality of the residuals left behind in the post-harvest stands. The current mechanized logging techniques also need to be improved by adopting the reduced impact logging (RIL) techniques, so as to promote regeneration of desired commercial timber species and as a consequence, sustainability of the forests.